Policy Innovation Model Integrated Village Program in Sukaraya Village, Bone-Bone, North Luwu District - Nuryanti Mustari; Herman Herman; Ulfiah Syukri; Muhammad Fahmi Fajar (Jurnal Ilmu Pemerintahan)
The study aimed to find out the diffusion of integrated village independent innovation (independent integrated village case study in North Luwu district). The informants in this study consisted of 3 people. The type of this study used was a qualitative approach, namely a study that using holistic-conceptual symptoms obtained through the results of collecting data from a natural background as a source with the instrument itself with the type of phenomenological research, that was a study conducted through exposure and experience experienced by informants with support qualitative data. The data collection techniques used were observation, interview, and documentation. The results of the study showed that the diffusion of independent integrated village innovation four indicators namely, innovation, communication channels, timeframes, and social systems do not work well and effectively on the implementation of independent integrated village innovation.